Body Temperature, Cutaneous Heat Loss, and Skin Blood Flow During Epidural Anaesthesia for Emergency Cesarean Section. Issue 3 (September 2019) - Mullington, C.J.; Low, D.A.; Strutton, P.H.; Malhotra, S.
Abstract : ( Anaesthesia . 2018;73:1500–15006) During the peripartum period, hypothermia and hyperthermia are both associated with adverse outcomes. Neuraxial anesthesia hinders a patient's ability to regulate body temperature by interrupting the sympathetic supply to the cutaneous vasculature. It is unclear how body temperature is affected by epidural administration of a concentrated local anesthetic for emergency cesarean section. This study aimed to determine how dosing of a labor epidural to provide anesthesia for cesarean section would affect mean body temperature and cutaneous vasomotor tone, hypothesizing that active cutaneous vasodilation would be blocked and therefore mean body temperature would increase.